Integrasi Ilmu Sosial dalam Tafsir Al-Qur’an: Pendekatan Interdisipliner dalam Kajian Kontemporer - Nabila Triastuty; Rolan Nasution; Suci Romadani Siregar; Wahyu Rahmadani Rambe (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of modern society, characterized by changes in the social, cultural, political, economic, and technological spheres, requires a Qur'anic interpretation that is capable of addressing contemporary issues in a relevant manner. Interpretive approaches that focus solely on textual aspects are often insufficient to explain the dynamic realities of society. Therefore, this article examines the integration of social sciences into Qur'anic interpretation through an interdisciplinary approach as an effort to enhance the relevance of contemporary tafsir studies. This study employs a qualitative method based on library research. The data were collected from various academic books and scholarly journal articles discussing contemporary tafsir methodology, interdisciplinary approaches, and the integration of social sciences into Qur'anic studies. The data were then analyzed using content analysis and a descriptive-critical approach to explore the contribution of social sciences to the development of Qur'anic interpretation. The findings indicate that the incorporation of perspectives from sociology, anthropology, political science, and economics helps connect the messages of the Qur'an with social realities. This approach broadens the scope of tafsir analysis and strengthens its ability to address contemporary humanitarian issues. Nevertheless, its application must remain balanced to prevent social theories from overshadowing the authority of the revealed text, while ensuring that established principles of tafsir methodology are maintained.